05B Radio Specialist Special Forces (Russian). Method for Determining Language Objectives and Criteria, Volume XII - Setzler, Hubert H., Jr.; Development and Evaluation Associates, Inc., Syracuse, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The position of radio specialist for special forces as performed in Russian is described in terms of terminal skill objectives (TSOs) and enabling objectives (EOs). This analysis is part of the communication/language objectives-based system (C/LOBS), which supports the front-end analysis efforts of the Defense Language Institute Foreign Language Center. The C/LOBS project, which is described in 13 volumes and an executive summary, functions as a subsystem of the instructional systems development approach currently in use in the TRADOC school system. Five job/duty positions and three languages were selected for field testing and system validation. This volume presents the results of the task analysis of Russian language requirements for radio specialist. The job tasks of this position use two communicative activities, briefing and teaching. These two communicative activities form the basic organizational scheme for the EOs. When the TSOs are mapped on the EOs either "briefs" or "teaches" provide organized and developed communicative strategies leading to mastery of the specific TSOs. The language functions critical to communicative task performance are referenced in the TSOs and the EOs. (SW)
Availability: Defense Language Institute, Foreign Language Center, Nonresident Instruction Division, Presidio of Montery, CA 93940.
Sponsoring Agency: Defense Language Inst., Monterey, CA.
Contract Number: DAAG39-77-C-0197.
ERIC Note: For related documents, see FL 010 789-802.
Microfiche.
Keywords: Communicative Competence (Languages); Educational Objectives; Higher Education; Instructional Systems; Language Usage; Languages for Special Purposes; Military Personnel; Notional Functional Syllabi; Occupational Information; Radio; Russian; Second Language Instruction; Skill Analysis; Systems Analysis; Systems Development; Training Objectives; Defense Language Institute CA; Language Skilled People; Reports, Research; Guides, Non-Classroom.